Induction Chemotherapy with Cisplatin and 5-Fluorouracil in Advanced Head and Neck Cancers: A Short Term Response Evaluation - Rao, Raghavendra (J Clin Diagn Res, 2015)
BACKGROUND: Considering the uprising number of Head and neck cancer in the state with limited options of medical and surgical treatment, the focus of this study involved on chemotherapy in advanced Head and neck cancers. The aim of this study was to evaluate the efficacy and toxicity of combination of Cisplatin and 5-Fluorouracil (PF) as induction chemotherapy in patients in locally advanced squamous cell cancer of head and neck. MATERIALS AND METHODS: Forty four patients with previously untreated stage III -IV advanced and inoperable cases were included in this prospective study. Induction chemotherapy consisted of 3 cycles of Cisplatin 100mg/mt(2) as infusion on day 1, 5-Fluorouracil of 750mg/mt(2) on day 2, 5-Fluorouracil of 1000mg/mt2 as infusion on day 3 in an inpatient basis. Cycles were repeated with an interval of 21 days. Patients were evaluated within a period of 3 weeks at the end of completion of third cycle of chemotherapy. Post chemotherapy local therapy was individualized based on the response, site and stage of the tumour. RESULTS: Out of 44 eligible and evaluable patients, major dominance was noted in male group constituting 68%. After induction chemotherapy 58.8% of stage III experienced stable response, & 44% had partial response. In stage IV, 44% showed a stable response and 33.3% had partial response. But in comparison to primary tumour response and nodal response, which had a significant clinical response, the overall response of malignancy with respect to stage and site specificity was clinically insignificant. Moderate adverse reaction was noted in 47.6% and 42.1% had mild reactions. Majority of patients experienced grade 3 adverse events, of which anaemia in females and leucopenia in males pre-dominated. CONCLUSION: With the use of cisplatin and 5-FU as induction chemotherapy agents in advanced and inoperable squamous cell carcinoma of head and neck, a distinct benefit was seen in stabilizing the tumour from progression. But achieving a significant complete response to the same is of faint possibility. An alternate multidrug regimen or multimodality treatment would be ideal to gain the optimum results from induction agents. Toxicity related to chemotherapy usually is transient at therapeutic doses, and can be controlled by adequate prophylactic measures.